2018
DOI: 10.1007/s13197-018-3065-6
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin isolated from A. americana encodes Human and Aspergillus oryzae S2 α-amylase inhibitions: credible approach for antifungal and antidiabetic therapies

Abstract: extract was analyzed by reverse phase HPLC for characterization. Among phenolic compounds identified, apigenin was observed to be present. The finding showed an inhibitory effect of apigenin towards Human and S2 α-amylases. Apigenin inhibition towards Human and α-amylase activities was observed to be competitive. IC50 and  % inhibition of apigenin for α-amylase were 3.98 and 1.65 fold higher than for Human α-amylase. The inhibition of the described biocatalyst activity was significantly lowered when apigenin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Depending on the characteristics of the isolated molecule, the bioactive potential is selective. A. oryzae α-amylase was more inhibited by the isolated compounds puerarin and apigenin from this plant species (95).…”
Section: Discussionmentioning
confidence: 84%
“…Depending on the characteristics of the isolated molecule, the bioactive potential is selective. A. oryzae α-amylase was more inhibited by the isolated compounds puerarin and apigenin from this plant species (95).…”
Section: Discussionmentioning
confidence: 84%
“…Studies suggested that apigenin, one of the flavones, may play an anti‐diabetic role via facilitating GLUT‐4 translocation in skeletal muscles, 42 down‐regulating CD38 expression, 42 protecting β‐cell function through inhibition of inflammatory signalling pathways, 43‐45 modulating the activity of AMPK and related gene expression 46‐50 which in turn enhances peripheral insulin sensitivity, 42 and targeting PPARγ 43 and DPP‐4 51 . It is claimed that apigenin not only restrains α‐glucosidase, 52 but also binds to starch and hence ameliorates postprandial hyperglycaemia 53 . Apigenin may also protect vital organs against diabetes complications 42 …”
Section: Discussionmentioning
confidence: 99%
“…51 It is claimed that apigenin not only restrains α-glucosidase, 52 but also binds to starch and hence ameliorates postprandial hyperglycaemia. 53 Apigenin may also protect vital organs against diabetes complications. 42 Results of Khan et al study 54 showed protective effects of carnosol, anextract isolated from Artemisia, on Langerhans islets.…”
Section: Hypoglycaemicmechanismsofartemisiamentioning
confidence: 99%
“…Puerarin and apigenin isolated from this species showed greater inhibitory effects against A. oryzae α-amylase, while p-coumaric acid proved a major inhibitor to human α-amylase at IC 50 : 98.8 µM, with an inhibition rate 2.3 times higher than acarbose. Thus, isolated flavonoids may be used as therapeutic agents for postprandial glycemia [52,53].…”
Section: Polar Compounds: Phenols and Flavonoidsmentioning
confidence: 99%